Aws certified cloud practitioner study guide clf-c01 exam - Piper, Ben; Clinton, David (Sybex, 2019)
Set yourself apart by becoming an AWS Certified Cloud Practitioner Take the next step in your career by expanding and validating your skills on the Amazon Web Services (AWS) Cloud. The AWS Certified Cloud Practitioner Study Guide: Exam CLF-C01 provides a solid introduction to this industry-leading technology, relied upon by thousands of businesses across the globe, as well as the resources you need to prove your knowledge in the AWS Certification Exam. This guide offers complete and thorough treatment of all topics included in the exam, beginning with a discussion of what the AWS cloud is and its basic global infrastructure and architectural principles. Other chapters dive into the technical, exploring core characteristics of deploying and operating in the AWS Cloud Platform, as well as basic security and compliance aspects and the shared security model. In addition, the text identifies sources of documentation or technical assistance, such as white papers or support tickets.
Title from resource description page (Recorded Books, viewed July 08, 2019)
Keywords: Computers; Ordinateurs; computers; COMPUTERS / Certification Guides / General; Study guides